Investigation of Landfill Stability Under Unsaturated Conditions Using the Concept of Suction Stress - Mohammad Reza Motahari; Maryam Dahaqin (مدل‌سازی پیشرفته در مهندسی عمران)
As we know, landfills contain large amounts of various pollutants, and any instability or destruction on the landfill slope can lead to significant human and financial losses. In such conditions, pollution can easily spread in the environment and lead to an ecological disaster. Therefore, the sustainability analysis of the landfill slope is of great importance. Since, due to climatic conditions, the amount of rainfall and the level of groundwater, soils are generally in an unsaturated state, in this article, the sustainability of the landfill is investigated using the unsaturated theory by considering the concept of suction stress and coding in C# in the Geo-studio software environment. To properly model and design the landfill, the properties of the soil materials of the covering parts of the landfill surface and the impermeable barriers at the bottom were considered. The safety factor of the landfill slope in the dry state was obtained, then the changes in the safety factor at different volumetric moisture percentages for the unsaturated surface and bottom soils of the landfill were calculated, and the effect of reinforcing the clay layers of the cover and bottom of the landfill on the slope stability was also investigated. The results obtained indicate that the safety factor in the unsaturated state compared to the dry state increases significantly; also, in the area of unsaturated soils, with a decrease in the volumetric moisture percentage, the safety factor increases. The notable result is that in unsaturated soils, the safety factor does not necessarily increase with the occurrence of reinforcement.